Pengaruh Latihan Bench Dip Terhadap Kemampuan Passing Bola Basket Pada SMAN 1 Narmada Tahun 2020 - Andi Irawan; Dadang Warta Chandra Wira Kusuma; Nurtajudin Nurtajudin (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
The problem with this research is that the students' low shooting results are caused by their passing and shooting abilities that are still not optimal. This can be seen when students throw and catch, passing the ball often does not reach the given friend, deep passing is the key to the basketball game. The purpose of this study is to examine the significance of different samples with the formulation of the problem posed is to find out whether there is an effect of bench dip training on basketball passing abilities at SMAN 1 Narmada in 2020". The research method for taking subjects in this study is cluster random sampling, which is a sampling technique that selects an area or group as the sample. The samples used were male students who took part in basketball extracurricular with a total of 20 people. To obtain data in this study, the test method and the method of documentation were used. The data analysis method used is the t-test (t-test). The results of the study based on the results of the t-test (t-test) showed the calculated value of the t-test was 26.29, so the significance level was 5% and N was 20, it turned out that the number of rejection of the null hypothesis stated in the table was 2.069. This fact indicates that the value of t arithmetic from the results of data analysis of 26.29 is above the number of rejection of the null hypothesis which is 2.069. (T value = 26.29 > r table 2.069) it can be concluded that "There is an effect of bench dip training on basketball passing skills at SMAN 1 Narmada in 2020.